America's imagined revolution: narrative and politics in the historical novel of Reconstruction - Hughes, T. (2019)
This thesis explores late nineteenth- and early twentieth-century novels about Reconstruction in the American South, identifying a sub-genre of the historical novel dedicated to narrating Reconstruction as revolutionary history. Operating at the margins of political and historical fiction, the writers studied excavate generic and temporal registers in the historical novel that enable them imagine revolution in ways that eschew a narrative of transition designed to describe the bourgeois-democratic nation-state to the exclusion of plantation societies. The Introduction examines the ways in which Reconstruction and its literature seem to negate critical languages and narrative models for discussing revolution. In response, it lays out the formal parameters of the historical novel of Reconstruction, focusing on an anachronistic treatment of historical time which acts as a rubric for imagining revolutionary dynamics specific to plantation society. Each chapter pairs the political and literary lenses through which writers view Reconstruction as revolution. In Chapter One, George Washington Cable’s allegorical form is explored alongside his account of a shifting public/private divide in the South. Chapter Two analyses Albion Tourgée’s ambivalence towards the revolutionary state through his ironic account of sincerity as a means of describing social custom. Chapter Three reads Charles Chesnutt and Frances Harper’s adoption of the passing genre as expressive of the temporality of Reconstruction’s revolutionary event. Chapter Four investigates W.E.B. Du Bois’ long development of a counterfactual narrative of the peasant political subject, from his unpublished first novel Scorn: a Romance (1905) through Black Reconstruction (1935). By reading narrative form in relation to political, legal and historiographical accounts of Reconstruction, the thesis argues that these writers do important theoretical work in framing revolution as an afterlife of slavery. In part through a reading of Chesnutt’s The Marrow of Tradition (1901), the Conclusion elaborates on the aporetic nature of this theoretical work and its relationship to the kinds of revolutionary dynamic plotted through the thesis.